2013
DOI: 10.1017/s0956796813000130
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing semantic bidirectionalization via shape bidirectionalizer plug-ins

Abstract: Matsuda et al. (Matsuda, K., Hu, Z., Nakano, K., Hamana, M. & Takeichi, M. (2007) Bidirectionalization transformation based on automatic derivation of view complement functions. In Proceedings of the International Conference on Functional Programming. ACM Press, pp. 47–58) and Voigtländer (Voigtländer, J. (2009) Bidirectionalization for free! In Proceedings of Principles of Programming Languages. ACM Press, pp. 165–176) have introduced two techniques that given a source-to-view function provide an update p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Reflecting in-place updates is a non-trivial problem given complex forward transformations [10]. This limitation of updates can be relaxed to some extent by combining semantic and syntactic bidirectionalization [16,24]. We expect that a similar extension is also applicable to our proposal.…”
Section: Related Workmentioning
confidence: 97%
See 2 more Smart Citations
“…Reflecting in-place updates is a non-trivial problem given complex forward transformations [10]. This limitation of updates can be relaxed to some extent by combining semantic and syntactic bidirectionalization [16,24]. We expect that a similar extension is also applicable to our proposal.…”
Section: Related Workmentioning
confidence: 97%
“…The desirable laws are sometimes considered too restrictive [44,7] because a framework that supports structure changes (insertion and deletion of elements) of views is unlikely to be able to satisfy them (for example, consider a forward transformation map fst and source [("A", 2)], and consider what happens if we change a view from ["A"] to [] and then insert "A" again). In [16,24], where semantic bidirectionalization is combined with another bidirectionalization technique [12] aiming at structure updates, the composability and undoability laws are sacrificed. Further studies on the desirable laws in the presence of insertions and deletions can be found in [43,5,45].…”
Section: Desirable Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different flavors of bidirectionalization have been proposed: syntactic [20], semantic [21,22,33,41], and a combination of the two [35,36]. Syntactic bidirectionalization inspects a forward function definition written in a somehow restricted syntactic representation and synthesizes a definition for the backward version.…”
Section: Semantic Bidirectionalizationmentioning
confidence: 99%
“…The question then arises, how much information needs to be included in order to be invertible. This problem has recently deserved much attention in the programming language community (see, e.g., [26]). Our work here was inspired by the very similar view/query determinacy problem.…”
mentioning
confidence: 99%